(untitled) (Journal of Environmental Bioremediation and Toxicology, 2025)
Plastic is ubiquitous worldwide, and the development of bioplastics necessitates the use of biodegradable and renewable resources. This study focuses on creating and characterizing biodegradable films using varying concentrations of corn starch. The bioplastic films are plasticized with glycerol and citric acid, the latter serving as co-plasticizers in different proportions. Starch concentrations range from 5% to 20% w/v, glycerol concentrations from 5% to 25% v/v, and citric acid content from 1% to 5% w/v. The resulting bioplastics are applied to butter paper to analyse surface morphology, solubility, and water retention. The films blended with glycerol as a plasticizer consistently showed promising results. Introducing citric acid as a co-plasticizer led to a bioplastic film with reduced water retention properties. This study outlines a simple, novel, and cost-effective technique to produce bio-based plastic.